ANTIBACTERIAL EFFICACY OF SPHATIKA BHASMA AND BHASMA DERIVED SILVER NANOPARTICLES: A TRAD ITION AL REMEDY IN A MODERN FORM - MRUNALII J. MHASKEY,; VAISHALI U. THOOL, (The Bioscan, 2025)
The utilization of Ayurvedic Bhasma is well-established in managing chronic diseases, while the introduction of silver nanoparticles signifies a contemporary advancement with extensive applications in healthcare. This research study meticulously evaluated the antibacterial efficacy of Sphatika Bhasma and silver nanoparticles derived from Sphatika Bhasma against multidrug-resistant isolates of Pseudomonas aeruginosa (Gram-negative) and Enterococcus faecalis (Gram-positive) through a minimum inhibitory concentration (MIC) assay. Different concentrations—2.5, 5.0, and 10 mg for Bhasma and 2.5, 5.0, and 10 μg for silver nanoparticles were employed for this evaluation. Characterization of the Bhasma and AgNPs was performed using UV vis Spectroscopy and XRD analysis. The findings revealed that the Bhasma and silver nanoparticles exhibited significant antibacterial activity against the target isolates. Notably, Sphatika Bhasma showcased the highest zone of inhibition against P. aeruginosa at a concentration of 10 mg. In contrast, the highest level of growth inhibition for AgNPs was recorded against E. faecalis at a concentration of 10 μg. These results highlight the potential of Sphatika Bhasma and its nano-derivatives as antimicrobial agents and encourage further exploration of nanotechnology-based strategies to address the increasing challenge of antimicrobial resistance, particularly in bacterial infections.